ASYMMETRY IN INFLATION TARGETING - DENİZ, PINAR (My University, 2020)
Following the world financial crisis beginning in the last quarter of 2008, aggregate demand and commodity prices have declined sharply leading to a fast decline in world inflation. This different and new period reflects the rise in risk appetite leading to high fluctuations in the short term capital flows. World central banks revised their monetary policy to the changing conditions taking into account financial stability. In 2002, the Central Bank of Republic of Turkey adopted inflation targeting (in the implicit form) to maintain price stability. After 2008, parallel to the developments in global markets, the Turkish economy reflects decline in inflation rates. Together with the changes in the economic conditions, estimating monetary policy models in the form of constant-coefficient and symmetric specification may lead to erroneous interpretations. This study analyzes the existence of structural break(s) and asymmetric behavior for the 2003-2016 period. The paper also examines the monetary policy model under the New Keynesian DSGE model. The Turkish monetary policy investigated for the period presents October 2009 as the break point under different models and structural break tests. Asymmetric reactions to interest rate, output and exchange rate are observed which are suggesting changes in the monetary preferences of Central Bank of Republic of Turkey.

2008 yılının son çeyreğinde başlayan dünya mali krizinin ardından, toplam talep ve emtia fiyatları keskin bir şekilde gerilemiş, dünya enflasyonunda hızlı bir düşüşe yol açmıştır. Bu farklı ve yeni dönem, kısa vadeli sermaye akımlarında yüksek dalgalanmalara yol açan risk iştahındaki artışı yansıtmaktadır. Dünya merkez bankaları, para politikasını değişen koşullara göre finansal istikrarı göz önüne alarak revize etmişlerdir. 2002 yılında Türkiye Cumhuriyet Merkez Bankası, fiyat istikrarını sağlamak için enflasyon hedeflemesini (zımni olarak) kabul etmiştir. 2008’den sonra, küresel piyasalardaki gelişmelere paralel şekilde Türkiye ekonomisinde enflasyonda düşüş gözlenmiştir. Ekonomik koşullardaki değişikliklerle birlikte, para politikası modellerini sabit katsayılı ve simetrik tanımlı şeklinde tahmin etmek yanlış yorumlara neden olabilir. Bu çalışma, 2003-2016 dönemi için yapısal kırılmaların ve asimetrik davranışların varlığını analiz etmektedir. Çalışma ayrıca para politikası modelini Yeni Keynesyen dinamik stokastik genel denge modeli altında incelemektedir. Bu dönemde incelenen Türk para politikası, farklı modeller ve yapısal kırılma testleri altında Ekim 2009’u kırılma noktası olarak vermektedir. Faiz oranı, çıktı ve kur üzerindeki asimetrik reaksiyonlar, Türkiye Cumhuriyet Merkez Bankası’nın parasal tercihlerinin farklılaştığını göstermektedir.
ENFLASYON HEDEFLEMESİNDE ASİMETRİ